Does attending elite colleges matter in the relationship between self-esteem and general self-efficacy of students in China?. Issue 6 (June 2022) - Zhang, Wenjie; Gao, Wenjuan; Liu, Xinqiao
Abstract: This study analyzed the reciprocal relationship between self-esteem and general self-efficacy among students from both the elite and non-elite universities in China. Descriptive statistics showed that the levels of general self-efficacy remained stable among Chinese college students albeit with minor fluctuations, while their self-esteem continuously declined during the four academic years; students from elite universities had higher self-esteem than their counterparts from non-elite universities. Moreover, the general self-efficacy of students was significantly and positively correlated with their self-esteem at college. Using a four-wave cross-lagged model, we found that the self-esteem and general self-efficacy among elite university students reinforced each other from the freshman to the junior years, whereas the self-esteem of their equivalents from non-elite universities monodirectionally predicted their subsequent general self-efficacy levels from the sophomore to the senior years. The study adds to the literature by (1) exploring the directionality of the relationship between self-esteem and generalized self-efficacy with four-wave panel data, and (2) discussing the heterogeneity of the relationship among sub-groups of the college students. The study proposed that institutions of different tiers should take targeted interventions to boost students' self-esteem and general self-efficacy. Highlights: The general self-efficacy of college students fluctuated over the four years. Self-esteem and general self-efficacy were significantly positively correlated. The two variables were evidenced to have reciprocal interactions with each other. The relationships were heterogeneous regarding the elite university attendance. Colleges should take targeted interventions to build general self-efficacy. Abstract : Elite university attendance; General self-efficacy; Self-esteem; College students.